Undescribed diversity in Iberian Mutillidae (Hymenoptera): a new species of Smicromyrme Thomson, 1870 from Portugal - Matias, Rafael (Zootaxa, 2024)
Mutillid wasps (Mutillidae) are relatively inconspicuous ectoparasitoid Hymenoptera, distributed worldwide, with ca. 150 species known from Europe. Compared to other areas in the continent (e.g. Italy, former USSR), and despite important effort made during the 20th century by Spanish entomologists, the biodiverse Iberian Peninsula remains relatively unexplored, with important knowledge gaps; this is particularly true and acute for Portugal, where prospection effort has been historically residual regarding the mutillid wasp fauna. The present situation at the regional level results from additional factors, including difficulties with diagnosing specimens, in turn also a consequence of insufficient original descriptions and from synonymies incorrectly established, creating taxonomic confusion. The synonymization of Mutilla pusilla Klug in Waltl, 1835 with various unrelated species by Ernest André was a particularly problematic case, causing several taxa to have remained undescribed for more than one century, confused under an incorrectly broadened definition. In consequence, the potential discovery of new taxa in the region is not unlikely and is maybe even expectable. Smicromyrme suarezi Matias, sp. nov. is described from females from Portugal and illustrated. The new species most closely resembles S. partitus Klug in Waltl, 1835 and S. sulcisius Invrea, 1955, both here also briefly treated and illustrated. Fourteen species of the genus Smicromyrme Thomson, 1870 are now known from the Iberian Peninsula; a key to their eight females is provided.